Pengaruh Transfer Ke Daerah, Kelahiran, Dan Pengangguran Terhadap Jumlah Penduduk Miskin Di Indonesia - Stephanus, Matthew; Muchtar, Masruri; Robinson, Pardomuan; Akhmadi, Muhammad Heru (Journal of Law, Administration, and Social Science, 2024)
Starting in 2004 with the issuance of the Law on Financial Relations between the Central and Regional Governments, the era of Regional Transfers also began. This transfer to the regions is expected to solve many problems of inequality in the regions that have not been reached by the central government. Based on BPS data in 2020, Indonesia's population reached 270 million with the percentage of poor people still in double digits. The pandemic from 2020 to 2022 also contributed to the increase in poverty. The pandemic in that year increased unemployment in the community which also contributed to poverty. In addition, the high birth rate, which according to several studies, is also a contributor to poverty. This research takes secondary panel data sourced from the Central Bureau of Statistics and the Directorate General of Fiscal Balance, the Ministry of Finance. This study uses the Random-Effect model by taking data for the period 2020 to 2022. The results showed that TKD, Birth, and Unemployment together had a positive impact on poverty. However, it was found that the unemployment variable had no significant effect. With this research, the government is expected to make TKD more targeted and control the birth rate.